Parameters optimization in compression molding of ultrahigh molecular weight polyethylene/cellulose nanofiber bionanocomposites by using response surface methodology - Sharip, Nur Sharmila; Ariffin, Hidayah; Andou, Yoshito; Kamal Bahrin, Ezyana; Jawaid, Mohammad; Md Tahir, Paridah; Ibrahim, Nor Azowa (Universiti Putra Malaysia Press, 2020)
Conventional UHMWPE molding involves long pressure holding duration, nevertheless in the presence of filler such as cellulose nanofiber (CNF), this may contribute to filler degradation. This study optimized the compression molding parameters of UHMWPE/ CNF bio-nanocomposite by using response surface methodology (RSM) in consideration of temperature, pressure and duration as variables. An optimal processing condition of 180°C, 15 MPa, and 20 minutes contributed to more than 80% desirability with tensile strength, yield strength, elongation at break, and Young’s modulus values of 22.83 MPa, 23.14 MPa, 487.31%, and 0.391 GPa, accordingly. Mechanical properties of UHMWPE/CNF bio-nanocomposites molded at optimized processing conditions were comparably similar to those prepared at conventional processing condition, and with the advantage of having shorter processing time. The results presented herewith provides insight towards a more practical approach for UHMWPE/CNF bio-nanocomposites consolidation process.